Choose your WoW! : a disciplined agile delivery handbook for optimizing your way of working - Ambler, Scott W., 1966-; Lines, Mark, 1964- (Project Management Institute, Inc., 2020)
"Hundreds of organizations around the world have already benefited from Disciplined Agile Delivery (DAD). Disciplined Agile (DA) is the only comprehensive tool kit available for guidance on building high-performance agile teams and optimizing your way of working (WoW). As a hybrid of all the leading agile and lean approaches, it provides hundreds of strategies to help you make better decisions within your agile teams, balancing self-organization with the realities and constraints of your unique enterprise context. The highlights of this handbook include: #1. As the official source of knowledge on DAD, it includes greatly improved and enhanced strategies with a revised set of goal diagrams based upon learnings from applying DAD in the field. #2 It is an essential handbook to help coaches and teams make better decisions in their daily work, providing a wealth of ideas for experimenting with agile and lean techniques while providing specific guidance and trade-offs for those "it depends" questions. #3 It makes a perfect study guide for Disciplined Agile certification. Why "fail fast" (as our industry likes to recommend) when you can learn quickly on your journey to high performance? With this handbook, you can make better decisions based upon proven, context-based strategies, leading to earlier success and better outcomes"-- Provided by publisher.
Keywords: Agile software development.; Project management.; Teams in the workplace.; elektronické knihy; electronic books